(untitled) (AYUSHDHARA, 2018)
Objective: Severe mental stress leads to enhanced platelet activation and endothelial dysfunction leading to Acute Coronary syndrome. This study is a population based, of subjects less than 40 years along with controls who are more than 40 years. Method: Young patients (≤ 40 years) and old patients (>40 years) admitted in hospital, during 2007-08 for ACS were chosen. After obtaining informed consent, they were administered Perceived stress scale and Life event stress scale questionnaire and based on the scores they were categorized as mild, moderate, and severely stressed. Results: The study population consisted of 88% males and 12% females. According to perceived stress scale, in young (≤ 40 years), almost 67 % of them had moderate stress and 24% of them had high stress, whereas in old (>40years), 78% of them had moderate stress and 20% had high stress. According to life event stress scale, in young almost 50% are moderate stressors and 33% are high stressors. However, in old 35% are having moderate stress and 60% are having severe stress. Though stress cannot be quantified this descriptive analysis, with the stress scales clearly showed that it is the precipitating factor in most of the young and old patients. It is also a causative factor for ACS in young patients (30%) without any significant risk factors. Conclusion: Stress seems to be significantly associated with ACS irrespective of age. It is acting mainly as precipitating factor and in certain cases as causative factor also.